2022
DOI: 10.3389/fonc.2022.782439
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs are Potential Prognostic Markers of Head and Neck Squamous Cell Carcinoma: Findings of a Meta-Analysis Study

Abstract: BackgroundSeveral studies have reported the role of circRNAs in the pathogenesis, diagnosis and prognosis of different cancers. This meta-analysis study aimed to evaluate the potential of using circRNAs as prognostic biomarkers of head and neck squamous cell carcinoma (HNSCC).Methods816 relevant articles were retrieved from PubMed and Science Direct databases, out of which 17 met the inclusion criteria. These 17 studies were assessed for quality by the Newcastle-Ottawa Scale (NOS) system, and 9 high quality st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…The wide availability and diversity of tissuespecific circRNAs (Lu et al have isolated and identified 21444 distinct circRNA from laryngeal squamous cell carcinoma [248]) has led to great interest and intensification of research. Nath et al reported nine different circRNAs dysregulated in HNSCC tumors that may serve as potential prognostic markers of HNC [249]. Similar findings have been reported for Laryngeal Squamous Cell Carcinoma [250,251], Tongue Cancer [252], Nasopharyngeal Carcinoma [253,254], Hypopharyngeal Squamous Cell Carcinoma [255] and Oral Squamous Cell Carcinoma [256,257].…”
Section: Circrnasupporting
confidence: 54%
See 1 more Smart Citation
“…The wide availability and diversity of tissuespecific circRNAs (Lu et al have isolated and identified 21444 distinct circRNA from laryngeal squamous cell carcinoma [248]) has led to great interest and intensification of research. Nath et al reported nine different circRNAs dysregulated in HNSCC tumors that may serve as potential prognostic markers of HNC [249]. Similar findings have been reported for Laryngeal Squamous Cell Carcinoma [250,251], Tongue Cancer [252], Nasopharyngeal Carcinoma [253,254], Hypopharyngeal Squamous Cell Carcinoma [255] and Oral Squamous Cell Carcinoma [256,257].…”
Section: Circrnasupporting
confidence: 54%
“…All the aforementioned intensive research and the attention gained by circRNA in relation to its role in HNC make it undoubtedly the second most popular, after microRNA, RNA molecule considered as a biomarker of the pathogenesis of head and neck cancers. Although miRNA is in the field of liquid biopsy at a much more advanced stage of research, circRNA is also considered an excellent biomarker, and the panels created as proposals for faster diagnostics [249] give hope for the usefulness of these molecules.…”
Section: Circrnamentioning
confidence: 99%
“…Further dual luciferase reporter experiments indicated that miR-30b-5p was the target of circPVT1. MiR-30b-5p participated in malignant progression in a variety of cancers including pancreatic cancer [15], esophageal squamous cell carcinoma [16], papillary thyroid cancer [17]. In this study, miR-30b-5p inhibitors partially reversed circPVT1 depletion-mediated inhibition in breast cancer cells.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, a previous study demonstrated that circRNA/miRNA/mRNA networks are involved in the development and progression of multiple types of malignancy (7). Results of a meta-analysis demonstrated that nine circRNAs may serve as potential prognostic markers for HNSCC and these are associated with lower overall survival (OS) and poor clinicopathological outcomes in patients with HNSCC (8).…”
Section: Introductionmentioning
confidence: 99%